8-2(3-t)=5t+4

Simplify each term.

Apply the distributive property.

8-2⋅3-2(-t)=5t+4

Multiply -2 by 3.

8-6-2(-t)=5t+4

Multiply -1 by -2.

8-6+2t=5t+4

8-6+2t=5t+4

Subtract 6 from 8.

2+2t=5t+4

2+2t=5t+4

Subtract 5t from both sides of the equation.

2+2t-5t=4

Subtract 5t from 2t.

2-3t=4

2-3t=4

Subtract 2 from both sides of the equation.

-3t=4-2

Subtract 2 from 4.

-3t=2

-3t=2

Divide each term in -3t=2 by -3.

-3t-3=2-3

Cancel the common factor of -3.

Cancel the common factor.

-3t-3=2-3

Divide t by 1.

t=2-3

t=2-3

Move the negative in front of the fraction.

t=-23

t=-23

The result can be shown in multiple forms.

Exact Form:

t=-23

Decimal Form:

t=-0.6‾

Solve for t 8-2(3-t)=5t+4